2014
DOI: 10.1007/s00345-014-1263-z
|View full text |Cite
|
Sign up to set email alerts
|

Urine protein profiling identified alpha-1-microglobulin and haptoglobin as biomarkers for early diagnosis of acute allograft rejection following kidney transplantation

Abstract: Protein profiling using mass spectrometry is suitable for noninvasive detection of rejection-specific changes following kidney transplantation. A specific protein profile enables the prediction of early acute allograft rejection in the immediate postoperative period. A1MG and Hp appear to be reliable rejection biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The AMBP gene encodes α 1 -microglobulin/bikunin precursor protein; α 1 -MG (A1M) is the lipocalin—derived from proteolytic cleavage of AMBP [24]. A1M is secreted into plasma, where it can exist free, or bound, to immunoglobulin-A or albumin.…”
Section: Lipocalin Family In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMBP gene encodes α 1 -microglobulin/bikunin precursor protein; α 1 -MG (A1M) is the lipocalin—derived from proteolytic cleavage of AMBP [24]. A1M is secreted into plasma, where it can exist free, or bound, to immunoglobulin-A or albumin.…”
Section: Lipocalin Family In Humansmentioning
confidence: 99%
“…Although the molecular weight of A1M is 27.0 kDa, it is freely filtered through the glomerulus and reabsorbed by proximal tubular cells [25]; for this reason, A1M is a biomarker of proteinuria, i.e., increased levels in urine indicate a defect in proximal tubules. A1M is considered to be a major factor for progressive impairment of renal function, as well as for early diagnosis of acute allograft rejection [13, 24, 26]. Recent studies have shown A1M to be expressed in rat retinal explants and to have oxygen radical-scavenging and reductase properties; these findings suggest that A1M might protect against oxidative stress and possibly be involved in the response to retinal detachment [27, 28].…”
Section: Lipocalin Family In Humansmentioning
confidence: 99%
“…HPT has been identified as a biomarker for several clinical outcomes, including acute allograft rejection [11], DN [21,22], chronic renal insufficiency [23], and glomerulonephritis. HPT is a heavily glycosylated alpha-2 sialoglycoprotein with a net negative charge [24].…”
Section: Discussionmentioning
confidence: 99%
“…AMBP is a stable urinary protein that has been used as a clinical parameter for the detection and differentiation of proteinuria. High-urine AMBP levels indicate proximal tubular dysfunction, and they are associated with interstitial fibrosis, tubular atrophy, and inflammation [11,21]. A previous study using ProteinChip (H50 chip) analysis has shown that urinary AMBP is increased in DN [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation